Breed and trace mineral source influence the performance of beef heifers during periods of nutrient restriction and grazing forage at early vegetative stage - Souza, Isabella R. T. [UNESP]; Moriel, Philipe; dos Santos, Taynara C. [UNESP]; de Miranda, André V. [UNESP]; Monar, Gabriel R. R. [UNESP]; Rezende, Maria E. [UNESP]; Augusto, Karolina V. Z.; Porcionato, Marco A. F.; Sanz-Fernandez, Maria Victoria; Souza, Izadora S.; Mackey, Shea J.; Cooke, Reinaldo F.; et al. (Oxford University Press (OUP), 2025)
We evaluated the effects of breed and mineral sources on heifer performance during periods of nutrient restriction and grazing. On day −7, ½ Angus × ½ Nelore (ANE) and Nelore (NE) heifers (12 heifers per breed; body weight, BW = 264 ± 35 kg; age = 15 ± 1 mo) were assigned to individual drylot pens to receive ad libitum Tifton 85 (Cynodon sp.) hay and white salt for 7 d. On day 0, within each breed, heifers were randomly assigned (2 × 2 factorial arrangement) to receive protein supplementation (0.20% of BW; dry matter, DM) added with sulfate (SUL) or hydroxychloride (HYD) sources of Cu, Mn, and Zn from days 0 to 49. From days 0 to 34, hay DM intake was restricted to 50% of the ad libitum intake recorded from days −7 to −1. On day 35, heifers were transferred to individual pastures to graze Tifton 85 forage at the early vegetative stage until day 49. No effects of breed × mineral source × day and breed × mineral source were detected (P ≥ 0.11). Nelore heifers had greater (P ≤ 0.02) average daily gain (ADG) from days 0 to 35 and days 0 to 49 compared to ANE heifers. Cumulative diarrhea incidence, fecal pH, and total days of diarrhea symptoms did not differ (P ≥ 0.19) between breeds. Nelore heifers had greater (P ≤ 0.05) serum concentrations of insulin-like growth factor 1 (IGF-1) from days 35 to 45 but had less (P ≤ 0.05) serum concentrations of cortisol and haptoglobin on days 42 and 45, respectively. Serum concentrations of urea N were greater (P ≤ 0.05) for NE vs. ANE heifers on days 0 and 42 and were less (P ≤ 0.05) for NE vs. ANE on days 38, 45, and 49. Heifers supplemented with HYD had (P ≤ 0.05) greater ADG from days 0 to 35, lower cumulative diarrhea incidence and percentage of heifers exhibiting ≥ 2 d of diarrhea from days 36 to 49, less serum concentrations of non-esterified fatty acids (NEFA) on day 35, and less serum concentrations of NEFA, cortisol, and urea N on day 38 compared to SUL heifers. In summary, breed influenced serum concentrations of haptoglobin, cortisol, urea N, insulin, and IGF-1, and the growth of beef heifers during nutrient restriction, but did not impact growth and incidence of diarrhea during periods of grazing forage at the early vegetative stage. Regardless of breed, replacing sulfate with hydroxychloride sources of Cu, Mn, and Zn led to minimal reductions in serum concentrations of NEFA, cortisol, and urea N, enhanced growth during nutrient restriction, and reduced diarrhea incidence during grazing of early vegetative forage.
Keywords: beef heifers; Bos indicus; hydroxychloride; sulfate; trace minerals